2008
DOI: 10.1038/hdy.2008.63
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric meiosis in pentaploid dogroses (Rosa sect. Caninae) is associated with a skewed distribution of rRNA gene families in the gametes

Abstract: In pentaploid dogroses, Rosa section Caninae (2n=5x=35), the pollen transmits one basic genome (x=7) derived from the seven segregating bivalents, whereas the egg transmits four basic genomes (4x=28) one set derived from the segregation of seven bivalents and three sets of univalent-forming chromosomes. Chromosomes from all five genomes carry 18-5.8-26S nuclear ribosomal DNA (rDNA) sites. This mode of sexual reproduction, known as permanent odd polyploidy, can potentially lead to the independent evolution of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…The sequences were aligned and checked for polymorphic sites (for the alignment matrix, see Supplementary Figure S1). In R. caesia and R. sherardii, essentially the same mutation hot spots (8-9) were identified as found in earlier ITS studies of R. canina, R. rubiginosa and R. dumalis (Kovarik et al, 2008b). In addition, four sites (À48, À119, À129, À156) were found to be highly polymorphic in the tetraploid R. mollis, whereas they were apparently monomorphic in the pentaploid species.…”
Section: Analysis Of Its From Gdna Clonessupporting
confidence: 58%
See 4 more Smart Citations
“…The sequences were aligned and checked for polymorphic sites (for the alignment matrix, see Supplementary Figure S1). In R. caesia and R. sherardii, essentially the same mutation hot spots (8-9) were identified as found in earlier ITS studies of R. canina, R. rubiginosa and R. dumalis (Kovarik et al, 2008b). In addition, four sites (À48, À119, À129, À156) were found to be highly polymorphic in the tetraploid R. mollis, whereas they were apparently monomorphic in the pentaploid species.…”
Section: Analysis Of Its From Gdna Clonessupporting
confidence: 58%
“…Polyploid dogroses contain both conserved and divergent rDNA types Our earlier study revealed the presence of multiple ITS families in three pentaploid species, R. canina, R. rubiginosa and R. dumalis (Kovarik et al, 2008b). In this study, we extended the analysis to two pentaploid (R. sherardii, R. caesia) and one tetraploid (R. mollis) species.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations